Analisis Vegetasi dan Persepsi Masyarakat Terhadap Rehabilitasi Hutan dan Lahan (RHL): (Studi Kasus di Desa Gunung Malang, Kecamatan Pringgabaya Kabupaten Lombok Timur) - Baiq Saupatu Hadawiah; Muhamad Husni Idris; Eni Hidayati (HUTAN TROPIKA, 2023)
This study is an attempt to determine the level of vegetation density resulting from the 2017 RHL planting in Gunung Malang Village. The study method for evaluating the plant density index is done by determining the number of sample plots based on Stratified Random Sampling is a technique used to determine the number of samples, if the population is stratified but not proportional. Taking into account the determination of the sample based on the potential of the arable land which then classified by taking three criteria, namely the potential with high, medium, and low levels which are classified based on secondary vegetation data of the cultivators. Data collection was carried out using a census inventory with Plot Samples were taken based on the area under cultivation. The results of the plant evaluation are then processed by calculating the density level index formula which is analyzed to obtain the value of Density and Relative Density (KR) to determine the density level of the area so that conclusions can be drawn. The results of the study show that the results of the analysis of the 2017 RHL vegetation density level of the remaining number are only 103 tree stands at this time with a density value of 2.4772 or (2.48%) with a relative density of 1 or (100%). From the results of the RHL density analysis, the density level was relatively low when compared to the number of seeds planted. With the current remaining stands, the percentage of growth is less than 75% of the total number of seedlings planted, so this RHL activity can be said to be unsuccessful based on PermenLHK No. 2 of 2020. Keywords; Evaluation, perception, Land and Forest Rehabilitation, Gunung Malang Village